Representasi Maskulinitas Pria dalam Iklan Kahf Edisi Life is a Journey #JalanYangKupilih (Analisis Semiotika Roland Barthes) - Utari, Maulida Dyah Nur; Amy Istiqlala Sophia Hikmah (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The concept of masculinity in men is typically associated with strong, brave physical traits, a disregard for appearance, and an adventurous spirit. Oftentimes, men feel constrained by this masculinity stereotype, leading them to overlook self-care. This stereotype has made men less inclined to consider using skincare products as they are seen as feminine and not in line with societal norms. However, the meaning of masculinity has shifted due to media influence conveying messages from various perspectives, including advertisements from brands. This shift is also influenced by the broader and more open-minded thinking of the audience. Masculinity is no longer confined to specific traits, allowing skincare brands targeting men to effectively convey their messages to the audience. This descriptive qualitative research delves into the meanings contained within an advertisement from the brand Kahf, specifically focusing on the